2006
DOI: 10.1097/01.pas.0000178094.07513.71
|View full text |Cite
|
Sign up to set email alerts
|

The Immunohistochemical Profile of Malignant Mesotheliomas of the Tunica Vaginalis

Abstract: Malignant mesotheliomas of the testis arise from the tunica vaginalis, formed from the evagination of the abdominal peritoneum into the scrotum. The immunohistochemical profile of the tunica vaginalis and associated neoplasms is often extrapolated from thoracic studies. Testicular series are uncommon, usually derived from previous case studies and literature reviews. The immunohistochemical findings in 20 cases originally diagnosed as malignant mesotheliomas are presented. Archival testicular malignant mesothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 34 publications
1
31
0
Order By: Relevance
“…The immunohistochemical markers that have been employed at other sites also apply to the examples of the tunica vaginalis, although it has been noted that thrombomodulin may not show as consistent a reaction pattern at this site. 291 The distinction of mesothelioma from reactive mesothelial hyperplasia may be problematic in this age group as in older patients. Mesothelial hyperplasia rarely produces a grossly apparent mass, unlike many mesotheliomas.…”
Section: Mesotheliomamentioning
confidence: 99%
“…The immunohistochemical markers that have been employed at other sites also apply to the examples of the tunica vaginalis, although it has been noted that thrombomodulin may not show as consistent a reaction pattern at this site. 291 The distinction of mesothelioma from reactive mesothelial hyperplasia may be problematic in this age group as in older patients. Mesothelial hyperplasia rarely produces a grossly apparent mass, unlike many mesotheliomas.…”
Section: Mesotheliomamentioning
confidence: 99%
“…A large immunohistochemical profile by Winstanley et al (2006) reported 18 cases of malignant mesothelioma specific to the tunica vaginalis from the UK between 1959 and 2004. They found that all cases were positive for calretinin (Figure 3) and EMA, 16 cases were positive for thrombomodulin, 15 cases were positive for CK7, 13 cases were positive for CK5-CK6, and all cases were negative for CK20 and carcinoembryonic antigen (CEA).…”
Section: Histopathologymentioning
confidence: 99%
“…Morphologically, most paratesticular mesotheliomas are epithelial, or mixed epithelial and sarcomatoid; with papillary, tubulopapillary or solid architectural patterns 2 3. Papillary mesotheliomas can be difficult to distinguish from papillary serous carcinoma on morphological grounds alone and usually require immunohistochemical and ultrastructural studies.…”
mentioning
confidence: 99%
“…Mesotheliomas are typically positive for calretinin, CK5/6, D2-40, vimentin and thrombomodulin but negative for BerEp4, LeuM1, CEA and CK20; whereas carcinomas typically show the reverse pattern 1 3–5. Rare BerEp4 and LeuM1 positivity is well documented in mesothelioma, although the staining is usually weak and focal 3. Ultrastructurally, mesothelioma cells typically contain long slender microvilli, abundant cytoplasmic filaments, including tonofilament bundles, desmosomal intercellular junctions and intracellular and intercellular lumina 1.…”
mentioning
confidence: 99%